1998
DOI: 10.2307/3579782
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Lesions and Other Products in X-Irradiated DNA Oligomers

Abstract: Free radicals interact with DNA bases to produce secondary radicals. The secondary radicals are reactive species and tend to interact with neighboring bases, resulting in DNA lesions with two adjacent modified bases. In this study the DNA oligomers d(CpApTpG) and d(CpGpTpA) were exposed to free radicals generated in anoxic aqueous solution by X irradiation. Four new lesions were identified in which adjacent guanine and pyrimidine bases are covalently bonded. One of the tandem lesions formed in d(CpGpTpA) has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 6 publications
2
65
2
Order By: Relevance
“…For instance, a G^T intrastrand crosslink lesion, where the C8 of guanine is covalently bonded to the methyl carbon of its neighboring thymine, was shown to be induced in calf thymus DNA upon γ irradiation (13). These previous studies also revealed that the intrastrand crosslink lesions are initiated from a single pyrimidine radical (9)(10)(11)13,(15)(16)(17). In this regard, hydroxyl radical ( · OH) can either be added to the C5 and C6 carbon atoms of cytosine, thymine and 5-methylcytosine, or abstract a hydrogen atom from the 5-methyl group of the latter two pyrimidine bases (21).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…For instance, a G^T intrastrand crosslink lesion, where the C8 of guanine is covalently bonded to the methyl carbon of its neighboring thymine, was shown to be induced in calf thymus DNA upon γ irradiation (13). These previous studies also revealed that the intrastrand crosslink lesions are initiated from a single pyrimidine radical (9)(10)(11)13,(15)(16)(17). In this regard, hydroxyl radical ( · OH) can either be added to the C5 and C6 carbon atoms of cytosine, thymine and 5-methylcytosine, or abstract a hydrogen atom from the 5-methyl group of the latter two pyrimidine bases (21).…”
Section: Introductionmentioning
confidence: 70%
“…The secondary radical of thymine can then couple with the C8 of the vicinal 5′ guanine to give rise to the G^T crosslink (8,10,12,13). Given that · OH can also result in the formation of single-base lesions, it is important for us to quantify both the single-base and the intrastrand crosslink lesions.…”
Section: Lc-ms/ms Identification and Quantification Of Dna Lesions Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent works have demonstrated that in dinucleoside monophosphates (11,12) and in oligonucleotides (11,13) peroxyl radicals of pyrimidine bases could efficiently react with a vicinal DNA base. Indeed, it has been recently reported that in DNA addition of pyrimidine peroxyl radicals onto the C8 of a purine base is capable of producing 8-oxodGuo involved in tandem lesions neighboring a formylamine (dF) residue (14,15).…”
mentioning
confidence: 99%